Net Promoter Score sebagai Tolok Ukur Ketercapaian Customer Loyalty Peserta Pekerja Penerima Upah Badan Usaha - Nur Imam Rhamdani (Jurnal Jaminan Kesehatan Nasional, 2021)
Abstract: The National Health Insurance Program (JKN) organized by BPJS Kesehatan is a program that developed rapidly at the beginning of its existence in terms of achieving membership coverage. To maintain the continuity of the program, indeed, proper management of customer services is required at each service point. This study was conducted to measure the level of satisfaction of participants whose results can be used as a basis for decision making. Measurement through the Net Promoter Score method is carried out, the results will describe the customers' willingness to recommend a product or service to others and represent customer loyalty itself. The measurement of the Net Promoter Score that has been carried out for customers who receive wages for business entities (PPU BU) at BPJS Kesehatan Tondano Branch Office shows high results (92.41% and 90%). With these results, it is hoped that BPJS Kesehatan can continue to improve existing services in areas of improvement that can be developed. The development of innovation based on the participant's point of view must be considered with a focus on service simplification and the implementation of information technology for the realization of a quality JKN program. Keywords: Customer loyalty; Net Promoter Score; BPJS Kesehatan